Would shared decision-making be useful in breast cancer screening programmes? A qualitative study using focus group discussions to gather evidence from French women with different socioeconomic backgrounds - Laureline Guigon; Laura X. Gil Sánchez; Anne-Sophie Petit; Alice Le Bonniec; Partha Basu; Christelle M. Rodrigue; Marie Préau; Patricia Soler-Michel; Patricia Villain (BMC, 2024)
Abstract Background To inform the development of an online tool to be potentially used in shared decision-making about breast cancer screening, French women were questioned about participation in breast cancer screening, the health professional's role, and their perceptions of the proposed tool. Methods We organised focus group discussions with 55 French women. Two different strategies were used to recruit women from high and low socioeconomic backgrounds. We applied both inductive and deductive approaches to conduct a thematic analysis of the discussions. We analysed the responses by using the main determinants from different health behaviour models and compared the two groups. Results Independently of socioeconomic status, the most important determinant for a woman's participation in breast cancer screening was the perceived severity of breast cancer and the perceived benefits of its early detection by screening. Cues to action reported by both groups were invitation letters; recommendations by health professionals, or group/community activities and public events were reported by women from high and low socioeconomic backgrounds, respectively. Among other positive determinants, women from high socioeconomic backgrounds reported making informed decisions and receiving peer support whereas women from low socioeconomic backgrounds reported community empowerment through group/community events. Fear of cancer was reported as a barrier in both groups. Among other barriers, language issues were reported only by women from low socioeconomic backgrounds; women from high socioeconomic backgrounds reported breast cancer screening-related risks other than overdiagnosis and/or overtreatment. Barriers to accessing the online tool to be developed were mainly reported by women from high socioeconomic backgrounds. Conclusion Limitations in implementing shared decision-making for women from low socioeconomic backgrounds were highlighted. An online tool that is suitable for all women, regardless of socioeconomic status, would provide "on-demand" reliable and tailored information about breast cancer screening and improve access to health professionals and social exchanges.